Construction of mathematical evolution model of components of transport system “man – automobile – environment” - Нагорний, Є.В.; Потапенко, А.В. (Eastern-European Journal of Enterprise Technologies, 2010)
The given work is devoted to the problem of the transport systems components forecasting. The problem solution is based on “man – automobile – environment” system evolution modeling.